Conducting Elections during COVID-19: New Policy Guidelines Issued by the Election Commission of India - Kumar Thakur, Bipin (HAPSc Policy Briefs Series, 2020)
The Election Commission of India (ECI) as per Article 324(1) of the Constitution of India has been vested with the power of superintendence, direction and conduct of all elections for the Parliament; State Legislatures and elections for the offices of the President and Vice-President. It had recently issued the Broad Guidelines for Conduct of General/Bye Elections during COVID-19. These Guidelines looked impressive to read but to implement them remained a difficult task; a lot depended on how the Election Commission, State administration including the police and health personnel conducted and fulfilled their due responsibilities. Their co-operation in a synchronized way has resulted in a successful exercise of conducting election in a difficult time and fulfilling a necessary prerequisite for a democratic government enshrined in our Constitution.